2018
DOI: 10.1007/s10973-018-7962-8
|View full text |Cite
|
Sign up to set email alerts
|

Reaction chemistry and kinetics of corn stalk pyrolysis without and with Ga/HZSM-5

Abstract: The bifunctional Ga/HZSM-5 catalyst has been proven having the capabiliity to increase the selectivity of aromatics production during catalytic pyrolysis of furan and woody biomass. However, the reaction chemistry and kinetics of pyrolysis of herbaceous biomass promoted by Ga/HZSM-5 is rarely reported. Pyrolysisgas chromatography / mass spectrometry (Py-GC/MS) analysis and nonisothermal thermogravimetric (TG) analysis at four heating rates were carried out to investigate the decomposition behavior and pyrolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Then, the secondary cracking reaction enhances the cracking of small volatile vapor molecules, affecting the formation of noncondensable gases. , Subsequently, the bio-oil yield increases to its highest value (33.23 wt %) at a temperature of 550 °C. At 600 °C, the bio-oil yield dramatically decreases to 26.37 wt % and moderately changes to 26.96 wt % at 650 °C due to the influence of the high temperature accelerating the secondary reaction of volatile vapor and depolymerization; thus, these are not suitable conditions for producing a high yield of bio-oil. ,, The solid yield shows a monotonically decreasing trend because the chemical bonds in the char matrix are disintegrated, causing a moderate decrease in the solid yield, while a small amount of coke forms during the secondary reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the secondary cracking reaction enhances the cracking of small volatile vapor molecules, affecting the formation of noncondensable gases. , Subsequently, the bio-oil yield increases to its highest value (33.23 wt %) at a temperature of 550 °C. At 600 °C, the bio-oil yield dramatically decreases to 26.37 wt % and moderately changes to 26.96 wt % at 650 °C due to the influence of the high temperature accelerating the secondary reaction of volatile vapor and depolymerization; thus, these are not suitable conditions for producing a high yield of bio-oil. ,, The solid yield shows a monotonically decreasing trend because the chemical bonds in the char matrix are disintegrated, causing a moderate decrease in the solid yield, while a small amount of coke forms during the secondary reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, both furan and furfural yields tend to decrease as the operating temperature increases, indicating that the presence of Cu on ZSM-35 contributed to the deoxygenation of furans and their derivatives into aldehydes and ketones and that further cracking affected hydrogen transfer, leading to enhanced formation of C 7 –C 12 hydrocarbons that manipulate the liquid yield of the aliphatic compounds. , ,, Furthermore, the synergistic effect of SCLs and LDPE at temperatures of 500–550 °C illustrated a positive effect on the bio-oil yield, and GC–MS analyses showed that the composition of the pyrolyzed bio-oil, which contained a proportion of aliphatic hydrocarbon compounds, resulted in the copyrolysis of SCLs and LDPE since the process conditions did not involve a higher temperature, which showed a positive synergistic effect. At low temperature, the thermal decomposition of LDPE to hydrocarbon radicals and anhydrosugar derivatives was enhanced from the thermal decomposition of lignocellulosics due to depolymerization into oligosaccharides, cleavage of its monomer, and deoxygenation. ,, Cleavage and rearrangement occur, and further cracking into low-molecular weight compounds, for example, furfural, noncondensable gases, and short alkane intermediates, occurs, while long alkanes might be produced by oligomerization or polymerization of short hydrocarbons. ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They deal with the kinetics of organic samples with highly complex chemical composition. A few recent works on similarly complex samples are also listed from the Journal of Thermal Analysis and Calorimetry [7][8][9][10][11][12][13][14]. Many further references can be found in the work of Cai et al [6] which is an overview of the application of the isoconversional methods for biomass pyrolysis till 2017.…”
Section: Introductionmentioning
confidence: 99%
“…It assumes one pool of reactants for which the reactivity varies as the reaction proceeds. However, most of the samples of practical interest contains more than one sort of reacting species, as it was the case in the studies [4][5][6][7][8][9][10][11][12][13][14] as well as in the nearly 100 works reviewed by Cai et al [6]. Each species has its own reacted fraction, its own reactivity parameters, and its own concentration in the sample.…”
Section: Introductionmentioning
confidence: 99%